PELATIHAN PENGGUNAAN MENDELEY BAGI GURU-GURU SD N CIBEBER 1 - Yusep Ahmadi; Gida Kadarisma (Abdimas Siliwangi, 2021)
This dedication is motivated by the fact that there are still many teachers who are not yet skilled and even don't know the reference management technique through Mendeley. Whereas in this era, ICT-based tools like Mendeley will be able to support the professionalism of a teacher. This service is in the form of training for elementary school teachers on the use of Mendeley in scientific articles. The aim of this training is to improve the knowledge and skills of elementary school teachers in the field of reference management in scientific articles using Mendeley tools. Mendeley is a software that functions as a reference and citation manager in scientific writings. The implementation of this service uses a structured training method. In addition, there is also an activity supplement in the form of independent mentoring for teachers who are still having trouble with joint training activities. The results of the implementation showed that this activity received a very good response. This can be seen from the very communicative training interactions. Based on questionnaire data before and after this training activity, it shows that the training participants experienced an increase in knowledge and skills by 30%. It can be concluded that this activity has been quite successful in improving teacher professionalism, especially in the field of ICT mastery such as Mendeley. This is also part of an effort to advance education, especially advancing teacher human resources at the basic education level